Current Role of Training in Robot-Assisted Urological Procedures. Issue 3 (July 2015) - Ficarra, Vincenzo; Abbinante, Maria; Giannarini, Gianluca; Rossanese, Marta; Crestani, Alessandro; Novara, Giacomo; Mottrie, Alexandre
The rapid introduction of robotic procedures necessitates new training methods. Currently, we can estimate that in a considerable proportion of the hospitals in Europe, the criteria for the surgeon's competence before starting with robotic surgery are insufficient. Therefore, the development of structured robotic training programs should be considered as one of the priorities that the urologic community must take into account in the near future.